Pneumonia Severity Index (PSI), CURB-65, and mortality in hospitalized elderly patients with aspiration pneumonia - Sehlhoff, B.; Niklaus, D.; Pientka, L.; Thiem, U.; Heppner, Hans Jürgen (Zeitschrift für Gerontologie und Geriatrie, 2011)
Background: Aspiration pneumonia is associated with a high morbidity and mortality in elderly patients. In order to provide risk-adapted medical care, it is necessary to establish valid prognostic tools for these patients. Objective: The value of two well-established scores to assess prognosis in community-acquired pneumonia (CAP), i. e., CURB-65 and the Pneumonia Severity Index (PSI), was evaluated in elderly patients hospitalized for aspiration pneumonia. Material and methods: A total of 209 patients hospitalized with aspiration pneumonia between 2001 and 2005 in a single center were evaluated using PSI and CURB-65. For comparison of morbidity and mortality, an equally large group of inpatients with CAP was analyzed. Results: The mean age of patients with aspiration pneumonia was 76.7±13.4 years, and 104 (49.8 %) were female. Patients with aspiration pneumonia more frequently showed a history of cancer, hypotension, and hyponatriemia on admission. Mortality was clearly higher in comparison to patients with CAP (39.2% vs. 16.3%). The Odds Ratio (OR) for mortality was 1.03 (95% CI 0.59; 1.79) for a CURB-65 score of 3-5 points compared to 0-2 points. In cases of CAP, OR showed a statistically significant increase of risk (OR 2.50; 95% CI 1.04; 6.06), for CURB-65 scores of 3-5 points vs. 0-2 points). In aspiration pneumonia, the PSI showed a trend towards increasing mortality within higher risk class. Conclusions: In geriatric patients hospitalized with aspiration pneumonia, CURB-65 and PSI have no prognostic value. © 2011 Springer-Verlag.
CRIS-Team Scopus Importer:2022-09-26
Keywords: Aspiration pneumonia; Community-acquired pneumonia; Elderly; Geriatrics; Prognosis